Searching for global equilibrium: How new economic statecraft undermines international institutions - Vinod K. Aggarwal; Andrew W. Reddie (Asia and the Global Economy, 2024)
The rise of “new economic statecraft”—intervention in trade and investment for foreign policy reasons—is increasingly threatening the stability of the global economic system. Building on previous work, we consider the types of intervention we have seen, classifying state measures as behind the border, at the border, and beyond the border. In addition, in the past, we have focused on understanding variation in new forms of economic statecraft through a five-factor model. This paper's central goal is to evaluate alternatives for constraining economic statecraft via institutional approaches. To this end, we draw on an analytical classification framework to theoretically and empirically analyze both sectoral and overall bilateral, minilateral, and multilateral institutional approaches to glean lessons for the management of new economic statecraft.